Stick and stone on the go ebook - Ferry, Beth (Stick and Stone., 2023)
Two stories in one graphic novel perfect for beginning readers, based on the bestselling Stick and Stone series by Beth Ferry and Tom Lichtenheld. For fans of the Narwhal series and Baloney and Friends. Stick would go anywhere with his best friend, especially if they're planning a picnic. But when picnics involve lemons and bees and caves, Stone's not so sure . . . Join Stick and Stone as they go spelunking. Accompany them as they meet all sorts of new friends, including a big, fluffy monster! And laugh along with them in this new graphic novel series starring two best buddies who know that exploring is always more fun when you're together. Each story has a fun activity to make you feel part of the action. Don't miss Stick and Stone's picture book adventures: Stick and Stone Stick and Stone: Best Friends Forever! Plus don't miss the young graphic novels: Stick and Stone Explore and More Stick and Stone on the Go